How First and Second Languages Influence Indonesian Students’ English as a Third Language: Transfer and Interference Analysis - Purba, Andiopenta (Elsya : Journal of English Language Studies, 2022)
In the face of the scarcity of linguistic studies on Batak Toba language, this study tries to contribute by investigating how Batak Toba students’ local language and mother tongue’s elements are transferred to their English as a foreign language output. Specifically, this study aims to describe the transfer and interference of Batak Toba and Indonesian as first and/or second language and how they influence learners’ English as a third language. The study observed 15 English Education programme students who were selected via snowball sampling and analysed the way the students speak and translate a set of phrases to their respective second and third languages. Results indicated that the students’ first and second languages interferes with their English language performance at the phonological, morphological, and syntactic levels. The novelty of this study is that it offers a detailed investigation of how students whose first language, Batak Toba, and second language, Indonesian, interfere with the foreign language that is a mandatory subject in the country’s formal education system, namely English. Recommendations for teachers, particularly teachers of Indonesian learners whose students are primarily bilingual and multilingual, are discussed.